Arabic Learning Material Design - Herdah Herdah; Raodhatul Jannah; Ashar Ashar (Universitas Muhammadiyah Enrekang, 2023)
Learning Arabic is a complex and challenging process for many students. To increase the effectiveness of learning, innovative and well-structured material design is needed. This article focuses on reviewing the design of Arabic learning materials. The research analysis method used in this paper is the literature analysis method, and it is concluded that the concept of learning material design is a planning process that includes several stages. First, determine learning objectives that are focused on newly learned knowledge, skills, and attitudes. Second, choosing the right methods, media, and materials to achieve these goals and adjusting to the curriculum or competency standards and basic competencies. In this case, it is necessary to consider other supporting sources, such as relevant learning resources and appropriate learning environments. Third, conduct a theory review and have a learning method that is suitable for students. Fourth, consider availability and accessibility and Fifth, develop the design into reality through the development process. This stage includes making clear and detailed blue-print documents and conducting sample trials.